Role for Gag-CA Interdomain Linker in Primate Lentiviral Replication - Doi, Naoya; Koma, Takaaki; Adachi, Akio; Nomaguchi, Masako (Frontiers in Microbiology, 2019)
Gag proteins underlie retroviral replication by fulfilling numerous functional roles at various stages during viral life cycle. Out of the four mature proteins, Gag-capsid (CA) is a major component of viral particles, and has been most well studied biogenetically, biochemically and structurally. Gag-CA is composed of two structured domains, and also of a short stretch of disordered and flexible interdomain linker. While the two domains, namely, N-terminal and C-terminal domains (NTD and CTD), have been the central target for Gag research, the linker region connecting the two have been poorly studied. We recently have performed systemic mutational analyses on the Gag-CA linker region of HIV-1 by various experimental and in silico systems. In total, we have demonstrated that the linker region acts as a cis-modulator to optimize the Gag-related viral replication process. We also have noted, during the course of conducting the research project, that HIV-1 and SIVmac, belonging to distinct primate lentiviral lineages, share a similarly biologically active linker region with each other. In this brief article, we summarize and report the results obtained by mutational studies that are relevant to the functional significance of the interdomain linker of HIV/SIV Gag-CA. Based on this investigation, we discuss about the future directions of the research in this line.